2020
DOI: 10.1007/s10530-020-02288-4
|View full text |Cite
|
Sign up to set email alerts
|

Historical museum collections help detect parasite species jumps after tilapia introductions in the Congo Basin

Abstract: This study highlights the value of museum collections in invasion biology. It focuses on introduced tilapias, Oreochromis niloticus and Coptodon rendalli in the Congo Basin and their monogenean (Platyhelminthes) gill parasite fauna. Oreochromis niloticus was introduced throughout the Congo Basin while C. rendalli was introduced into the Lower Congo, but is native to the Middle and Upper Congo. In order to study the impact of these stocking events on the native parasite community we investigate the co-introduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 56 publications
1
53
0
Order By: Relevance
“…Fish specimens belonging to Cichlidae Bonaparte, 1835 (Cichliformes), the nothibranchiid genus Aphyosemion Myers, 1924 (Cyprinodontiformes: Nothibranchiidae), and Polycentropsis abbreviata Boulenger, 1901 (Ovalentaria, incertae sedis: Polycentridae) were collected during various expeditions across Africa between 2008 and 2019 and from few specimens from aquaculture facilities in France (Appendix 1). As samples collected during these expeditions have been included in previous studies, sampling details can be found in the respective publications (Vanhove et al 2011(Vanhove et al , 2013Muterezi Bukinga et al 2012 ; Pariselle et al 2015aPariselle et al , 2015bJorissen et al 2018aJorissen et al , 2018bJorissen et al , 2020. We dissected the (which was not certified by peer review) is the author/funder.…”
Section: Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Fish specimens belonging to Cichlidae Bonaparte, 1835 (Cichliformes), the nothibranchiid genus Aphyosemion Myers, 1924 (Cyprinodontiformes: Nothibranchiidae), and Polycentropsis abbreviata Boulenger, 1901 (Ovalentaria, incertae sedis: Polycentridae) were collected during various expeditions across Africa between 2008 and 2019 and from few specimens from aquaculture facilities in France (Appendix 1). As samples collected during these expeditions have been included in previous studies, sampling details can be found in the respective publications (Vanhove et al 2011(Vanhove et al , 2013Muterezi Bukinga et al 2012 ; Pariselle et al 2015aPariselle et al , 2015bJorissen et al 2018aJorissen et al , 2018bJorissen et al , 2020. We dissected the (which was not certified by peer review) is the author/funder.…”
Section: Samplingmentioning
confidence: 99%
“…These introductions might also increase the chances of co-introduction for their parasites and create more opportunities for host range expansions (e.g. Jorissen et al 2020). To avoid these biases, (which was not certified by peer review) is the author/funder.…”
Section: Systematic Informativeness Of Morphometric Measurements and mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that in a single species, P. trachuri, we found specimens with and without what look like "multiple lateral vaginae", we believe that the taxa mentioned above, and probably others, should be re-examined, preferably using both morphology and molecular information. More generally, we stress the importance of integrative taxonomy [21] for the taxonomy of parasites, including correct identification of hosts using both morphology and molecular analysis as in the present work and recent studies [5,[8][9][10]43] and, whenever possible, deposition of hosts in curated collections [12,36,39,42].…”
Section: Comments On Other Generamentioning
confidence: 77%
“…Nile tilapia (O. niloticus), in particular, is becoming established across Africa outside of its natural range, including in South Africa (D'Amato et al, 2007), Zambia (Deines et al, 2014), Zimbabwe (Marufu & Chifamba, 2013), the Democratic Republic of Congo (Goudswaard et al, 2002;Mamonekene & Stiassny, 2012), Kenya (Angienda et al, 2011), as well as Tanzania , with reports of either replacement of the native species or extensive introgressive hybridization (Bradbeer et al, 2019;Shechonge et al, 2018). There is also evidence of parasite transmission from introduced tilapia species to native species (Jorissen et al, 2020). Despite this, intentional movement and stocking of tilapia species into natural water bodies continues in many regions of Africa (Genner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%